Aggressive rhabdomyosarcoma of palate: A case report and literature review - Hari Ram; Shalini Gupta; Shadab Mohammad; Akhilesh Chandra (Wolters Kluwer Medknow Publications, 2014)
Rhabdomyosarcoma (RMS) is the most common soft tissue sarcoma encountered in childhood and adolescence. The common sites of occurrence are the head and neck region, genitourinary tract, retroperitonium and the extremities. Orbit, paranasal sinuses, cheek, and the neck are the common affected site in head and neck region. RMS is relatively uncommon in the oral cavity, and the involvement of the jaws is extremely rare. Multidisciplinary approaches surgery, chemotherapy and radiotherapy, are use for treatment. Here, we report an aggressive form of RMS at palate of a 9 months old female child which did not respond to chemotherapy.